Pioneers of Breast Implant-Associated Anaplastic Large Cell Lymphoma: History from Case Report to Global Recognition - Miranda, Roberto N. (2019)
The first case of breast implant-associated anaplastic large cell lymphoma (breast implant ALCL) was described by John Keech and the late Brevator Creech in 1997. In the following 2 decades, much research has led to acceptance of breast implant ALCL as a specific clinicopathologic entity, a process that we bring up to life through the memories of 6 persons who were involved in this progress, although we acknowledge that many others also have contributed to the current state of the art of this disease. Dr. Keech recalls the events that led him and Creech to first report the disease. Ahmet Dogan and colleagues at the Mayo Clinic described a series of 4 patients with breast implant ALCL, and led to increased awareness of breast implant ALCL in the pathology community. Daphne de Jong and colleagues in the Netherlands were the first to provide epidemiologic evidence to support the association between breast implants and ALCL. Garry Brody was one of the first investigators to collect a large number of patients with the disease, present the spectrum of clinical findings, and alert the community of plastic surgeons. Roberto Miranda and L. Jeffrey Medeiros and colleagues studied the pathologic findings of a large number of cases of breast implant ALCL, and published the findings in 2 impactful studies in the medical oncology literature. The recognition and acceptance of this disease by surgeons, epidemiologists, and medical oncologists, working together, has led to subsequent studies on the pathogenesis and optimal therapy of this disease.